The Effect of Service Quality and Price on Customer Loyalty Through Customer Satisfaction as a Mediating Variable in Logistics Service Companies - Yuaningsih, Jerry Party; Cahyadi, Lukman (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Customer loyalty is crucial for companies operating in the logistics service industry. Service quality and pricing, as independent variables, along with customer satisfaction as a mediating variable, are important factors to consider in gaining loyal customers in the fast-paced era of globalization. This study aims to measure the influence of service quality and price on customer loyalty through customer satisfaction as a mediating variable at the logistics service company Lion Parcel. The research design employed a purposive sampling method involving 126 respondents who had previously used Lion Parcel logistics services. Data were analyzed using the Structural Equation Model (SEM) with SmartPLS 4.0. The findings indicate that service quality and price have a positive effect on customer satisfaction and customer loyalty. However, customer satisfaction does not have a significant effect on customer loyalty, nor does it mediate the relationship between service quality and price on customer loyalty.